Assessing Oral Health-Related Quality of Life in Older Tennessean Adults - Yeleeya Y. Li; Ying Liu; Memunat Ogunmefun; Kesheng Wang (Dentistry Journal)
Background: Tennessee has one of the worst rankings for older adults’ oral health in the United States. This study aims to evaluate the oral health-related quality of life (OHRQoL) among older individuals (aged 60 and above) in Tennessee using the Oral Health Impact Profile-14 (OHIP-14) questionnaire. Methods: The data were collected from the 233 Tennessee Smile-on program participants in the early phase of the COVID-19 pandemic, between December 2019 and August 2021. The frequency and percentage for each subgroup were calculated. Cronbach’s alpha was used to measure the internal consistency or reliability of OHIP in this study. Factor Analysis (FA) with oblique rotation was conducted to explore the underlying factor structure of the OHIP questionnaire set. A p < 0.05 was considered statistically significant. Results: The majority of participants were retired (59.66%), and there was a significant difference in OHIP_sum scores among different employment statuses (p = 0.018). Cronbach’s alpha showed the domains of psychological discomfort, physical disability, and psychological disability were highly correlated with the total score (alpha = 0.8). Factor analysis identified three main dimensions: physical discomfort, psychological distress, and functional disability, and they can explain over 90% of the total variance. Individuals measure of sampling adequacy (MSA) and overall MSA are greater than 0.9, indicating excellent sampling adequacy. Conclusions: The study suggested that oral health can be assessed not only through examinations by dental professionals but also by considering emotional and social well-being. However, a limitation of the study is that it was conducted during the COVID-19 outbreak, which restricted participant involvement.